2017
DOI: 10.1111/eip.12501
|View full text |Cite
|
Sign up to set email alerts
|

Negative symptoms of psychosis: A life course approach and implications for prevention and treatment

Abstract: Similar to other aspects of schizophrenia, negative symptoms likely involve a complex interplay of several risk and protective factors at different life phases. Concepts suggested in this article, such as "negative symptom reserve" theory, require further research, which may inform future prevention and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 140 publications
2
20
0
1
Order By: Relevance
“…In addition to the sum score of core NS, the group effect became significant for items N1, N4 and D4, though only at a small to moderate effect size (Rosenthal's r: 0.196-0.235). Furthermore, longitudinal analyses revealed that, in line with reports in other clinical samples (Lyne et al, 2018), core NS predominately remained stable over time (i.e. persistently absent or present at baseline and follow-up in 73% of cases).…”
Section: Prevalence Severity and Course Of Ns In 22q11dssupporting
confidence: 82%
See 1 more Smart Citation
“…In addition to the sum score of core NS, the group effect became significant for items N1, N4 and D4, though only at a small to moderate effect size (Rosenthal's r: 0.196-0.235). Furthermore, longitudinal analyses revealed that, in line with reports in other clinical samples (Lyne et al, 2018), core NS predominately remained stable over time (i.e. persistently absent or present at baseline and follow-up in 73% of cases).…”
Section: Prevalence Severity and Course Of Ns In 22q11dssupporting
confidence: 82%
“…Interesting, these numbers are in line with the trajectory of positive symptoms (see also Schneider et al, 2013;Tang et al, 2017), which might indicate a stronger co-variance of positive and negative symptoms in 22q11DS than in other clinical populations (in the present study, the course of positive and negative symptoms between baseline and follow-up was similar in almost 40% of the sample). In patients with psychosis, at least in the longer term, negative and positive symptoms likely have an independent longitudinal course, with negative symptoms displaying greater stability over time (Lyne et al, 2018). Future studies should explore in greater details the developmental course of psychotic symptoms over time in 22q11DS.…”
Section: Prevalence Severity and Course Of Ns In 22q11dsmentioning
confidence: 99%
“…The current study was correlational; thus, the mechanisms through which negative symptoms and working memory affect social and role functioning are still not well understood. A parsimonious explanation is that there is often overlap in content between measurement of negative symptoms and cognitive, social, and role functioning [60,61]. For example, the Scale for the Assessment of Negative Symptoms (SANS) [62] includes items assessing impaired attention, and the Clinical Assessment Interview for Negative Symptoms (CAINS) [63] includes items assessing motivation and pleasure for social, recreational, and vocational activities.…”
Section: Discussionmentioning
confidence: 99%
“…Most sessions were applied in patients with ADHD (about 30 sessions), whereas number of sessions was smaller in patients with schizophrenia (10–20 sessions). Possibly, patients with ADHD are more able to undergo a large number of treatment sessions then patients with schizophrenia, which are more disabled when it comes to adhering treatment due to their negative symptoms ( 53 ). In the study by Nan et al ( 50 ), an intense 4-day neurofeedback training protocol was applied.…”
Section: Discussionmentioning
confidence: 99%